Consumption According to The Perspective of The Qur’an and The Sunnah of The Prophet Muhammad SAW - Mutaqin, Enjen Zaenal (Wealth: Journal of Islamic Banking and Finance, 2024)
This research aims to provide a deeper understanding to the public, especially Muslims, regarding the ethics of consumption in everyday life in accordance with Islamic law, namely according to the perspective of the Qur'an and the sunnah of the Prophet Muhammad SAW so that it can bring blessings to the food or drink consumed. . This study uses a descriptive qualitative approach by comprehensively examining the sources of material about consumption contained in the Qur'an and hadith. This research is focused on discussing how consumption ethics, consumption principles in Islam and consumption limits are in accordance with Islamic law. In the context of consumption activities, an understanding of good and correct consumption procedures in accordance with Islamic law is very necessary in order to bring health, safety and blessings to life. It is hoped that this article can provide additional knowledge and in-depth understanding of consumption in Islam so that it can help the Muslim community in practicing religious law, especially consumption ethics in a better way in order to obtain the blessing of Allah SWT.